2008
DOI: 10.1007/s00535-008-2214-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of omeprazole in Japanese patients with nonerosive reflux disease

Abstract: Omeprazole 10 mg or 20 mg once daily is effective and well tolerated in patients with NERD regardless of their endoscopic classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 24 publications
(29 reference statements)
8
31
0
Order By: Relevance
“…There were, however, no differences in measures of QOL or depression and anxiety between the two treatment groups. Studies of PPI therapy in predominantly Caucasian, Western patients with NERD have found a complete symptom resolution rate of 29.3-59%, and a satisfactory symptom resolution rate of 56.7-73% [13,[15][16][17]; similarly, studies in the Japanese population found complete response rates of between 25.8 and 44% [18,19]. Our rate of complete symptom resolution was 24.4% and the rate of satisfactory symptom resolution was 57.1%.…”
Section: Discussionsupporting
confidence: 50%
“…There were, however, no differences in measures of QOL or depression and anxiety between the two treatment groups. Studies of PPI therapy in predominantly Caucasian, Western patients with NERD have found a complete symptom resolution rate of 29.3-59%, and a satisfactory symptom resolution rate of 56.7-73% [13,[15][16][17]; similarly, studies in the Japanese population found complete response rates of between 25.8 and 44% [18,19]. Our rate of complete symptom resolution was 24.4% and the rate of satisfactory symptom resolution was 57.1%.…”
Section: Discussionsupporting
confidence: 50%
“…NERD accounts for at least half of GERD cases [3], but acid reflux has little role in the pathogenic mechanism [4], and with proton pump inhibitors (PPIs), which are the first choice of treatment in GERD [5,6], the symptom improvement rate in NERD is low [3,7,8,9]. In the pathogenesis of PPI-refractory NERD, which occurs in ≄50% of NERD patients, other than acidity, nonacid reflux, abnormal esophageal motility, esophageal hypersensitivity and psychological factors are intricately related [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the meta-analysis of 17 randomized controlled trials in which reflux patients were included and PPI was compared with the arms of surgery or placebo, no difference was observed in terms of all of the adverse effects (RR: 1.04, 95% CI: 0.98-1.11) (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). In the meta-analysis of 6 randomized trials in which H2RA and placebo were compared, the incidence of all of the adverse effects was similar among the arms (RR: 1.13, 95% CI: 0.97-1.31) (39)(40)(41)(42)(43)(44).…”
mentioning
confidence: 99%